Case Study : Ramly Food Processing Sdn Bhd / Wan Nur Athinia Ines Wan Fouzi - Wan Fouzi, Wan Nur Athinia Ines (2021)
Ramly Food Processing Sdn Bhd, also known as Perusahaan Burger Ramly Mokni Sdn Bhd, is a local food firm in Malaysia. The firm was started in 1984 by Dato' Dr Haji Ramly bin Mokni and Datin Hajjah Sahal Siah Abdul Manap, a husband and wife partnership, on a revolutionary platform to create Halal, sanitary, and high-quality items. Their goal is to create a halal western fast-food franchise in Malaysia that is both fresh and high-quality 'Pastikan Ramly Baru Beli' is the company's tagline. Ramly Food Processing Sdn Bhd began operations in 1979 at Lorong Haji Hussin in Kuala Lumpur, where it was formerly a modest firm with merely a mobile kiosk. Ramly Food Processing Sdn Bhd is well-known for their burger patties, which come in two flavors: beef and chicken. They are also a well-known Bumiputera enterprise that has been recognized three times by the Development Bank. In 1982, they received the Best Project Award, the Jaya Entrepreneur Award, and the Client Development Award in 1984. Ramly Processing Food Sdn Bhd has successfully released 1,000,000 burger patties every day in recent days. The firm operates a processing factory in Mukim Batu, Kuala Lumpur, which offers job possibilities in management, production, and product marketing and distribution. Kumpulan Ramly now has ten subsidiary firms under its umbrella. Thailand, Singapore, Bangladesh, Myanmar, Vietnam, and Indonesia have all received their merchandise. There are 16 Ramly Halal Marts and 12 Ramly Halal Kiosks in Malaysia, but they intend to open 450 more in the next several years. Even with competition from gourmet burger sellers, Ramly remains an iconic and accessible Malaysian meal whose appeal is unlikely to wane very soon.